Conficts In Condon’s Movie “Beauty and the Beast 2017” - Jesa Putri Yasari, Putu; Wandia, I Ketut; Isnu Maharani, Sang Ayu (Humanis, 2019)
The title of this paper is Conflicts in Condon’s Movie “Beauty and the Beast 2017” . It is aimed at finding out kinds of conflict faced by the main character and the sources of the main character’s conflict, and analyzing the way the main characters solve the conflict.  The data of this study were taken from a movie entitled “Beauty and the Beast 2017”. This study focuses on describing external and internal conflicts. The conflict is analyzed based on the theory of conflict proposed by Kenney who divides conflicts into two types, external and internal conflicts. The description of the presentation of the characters is analyzed based on the theory proposed by Deetz & Stevenson who divides it into two, those are the source of conflict and resolution of conflict. The result of this study shows that the main character faces two conflicts; external and internal conflict. The sources of the main character’s conflict are incompatible goals, and different opinions. In managing the conflict, the main character uses avoidance strategy, competition strategy and pacification.